THE EFFECT OF CHEMICAL ADDITIVES ON THE HARDENING OF PUTSOLAN PORTLAND CEMENT - Abdurahimov Abdukarim Abduhalimzoda; Abdumominov Odina Rashidovich (American Journals, 2023)
This article analyzes the data on the effective use of chemical additives to increase the strength of putsolan portland cement.
Keywords: chemical, additive, superplasticizer, pozzolan polishing cement, mineral